Design and Analysis of Decision Support Information System to Determine The Priority of Selecting Natural Disaster Barrack Policies With The Fuzzy Simple Additive Weighting Method - Muh Wahid Anshori Riza; Sholeh Hadi Pramono; Rahmadwati Rahmadwati (JAREE (Journal on Advanced Research in Electrical Engineering), 2019)
The lack of a disaster information system nowadays has made it difficult to find out information in the disaster area. Making information systems in disaster areas is important to solve the problem of uneven distribution of aid provided at each barrack. Because the conditions of each barrack are different, a system is needed to determine the priority for selecting disaster. To be able to determine the recommendations for the selection of disaster barracks, this study uses the Fuzzy Simple Additive Weighting (Fuzzy SAW) method, uses fuzzy method to determine the input basis value to SAW [3]. With the implementation of the Fuzzy SAW method, the results of this study can provide recommendations for Badan Penangguangan Bencan Daerah (BPBD) of Malang to determine the priority of disaster barracks that can take precedence.Keywords: disasters, fuzzy, information systems, priorities, simple additive weighting.